Pengaruh Emosional, Kepuasan, dan Kepercayaan terhadap Loyalitas Pelanggan pada Kantor Notaris dan PPAT Debora Ekawati Lukman Dadali, S.H - Jeny Yeolanda; Heryenzus Heryenzus (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of emotional, satisfaction and trust on customer loyalty. Adapaun who became the sample in this study were clients of the Office of Notary and PPAT Debora Ekawati Lukman Dadali, S.H., with a sample size of 170 clients. This research uses quantitative descriptive analysis method, while the data analysis used in this research is multiple linear regression analysis. The results of research on emotional variables have no effect and are partially significant to customer loyalty 0.693 < 1.654, then the results of research on satisfaction variables have no effect and are partially significant to customer loyalty 0.268 < 1.654, and the results of research on trust variables have a positive and significant effect on customer loyalty 3.692 > 1.654. While the results of research on emotional idependent variables, satisfaction and trust have a positive and significant effect simultaneously on the dependent variable of customer loyalty.